Thermally conductive silicone composition

The thermally conductive silicone composition, featuring a bismuth tin alloy and specific filler particle sizes, addresses the challenges of high thermal resistance and reliability issues in existing materials, achieving effective heat dissipation and stability for electronic components.

JP2025039021APending Publication Date: 2025-03-21SHIN ETSU CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023145754
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing thermally conductive materials for electronic components face challenges such as high thermal resistance, reliability issues due to filler particle size reduction after heat cycles, and the risk of corrosion from low melting point metals like gallium.

Method used

A thermally conductive silicone composition is developed, comprising a bismuth tin alloy powder and a filler with a specific average particle size, along with other components like organopolysiloxane and a catalyst, to achieve low thermal resistance and improved reliability.

Benefits of technology

The composition effectively reduces thermal resistance and enhances reliability by maintaining filler particle size stability through heat cycles, thus providing superior heat dissipation performance for electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039021000001
    Figure 2025039021000001
  • Figure 2025039021000002
    Figure 2025039021000002
  • Figure 2025039021000003
    Figure 2025039021000003
Patent Text Reader

Abstract

To provide a thermally conductive silicone composition which provides a cured product having low thermal resistance and excellent reliability.SOLUTION: There is provided a thermally conductive silicone composition comprising all of the following components (A) to (F): (A) an organopolysiloxane having at least two alkenyl groups at the ends of the molecular chain and a kinematic viscosity at 25°C of 100 to 500000 mm2 / s, (B) a hydrolyzable methylpolysiloxane having a trifunctional termination at one end represented by the following formula (1) (wherein, R1 is an alkyl group having 1 to 6 carbon atoms and a is a number of 5 to 100), (C) a bismuth-tin-based alloy powder having a melting point of 220°C or less, (D) a thermally conductive filler having a melting point of 280°C or more and an average particle diameter of 3 μm or more other than the component (C), (E) an organohydrogen polysiloxane having at least two hydrogen atoms (Si-H group) directly bonded to silicon atoms in one molecule, (F) a catalyst selected from platinum and a platinum compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive silicone composition that has high heat dissipation performance and is highly reliable. [Background technology]

[0002] It is widely known that electronic components such as LSIs and IC chips generate heat during use and the associated performance degradation, and various heat dissipation technologies are used as a means to solve this problem. For example, it is known that a cooling component such as a heat sink is placed near the heat generating component, and the two are placed in close contact to promote efficient heat transfer to the cooling component, thereby cooling the cooling component, thereby efficiently dissipating heat from the heat generating component. In this case, if there is a gap between the heat generating component and the cooling component, the heat transfer becomes inefficient due to the presence of air with low thermal conductivity, and the temperature of the heat generating component does not drop sufficiently. In order to prevent such a phenomenon, heat dissipation materials, heat dissipation sheets and heat dissipation greases that have good thermal conductivity and can follow the surface of the components are used to prevent the presence of air between the heat generating component and the cooling component (Patent Publication No. 2938428, Patent Publication No. 2938429, Patent Publication No. 3952184: Patent Documents 1 to 3). Among them, heat dissipation grease can be used with a thin thickness when mounted, and therefore exhibits high performance in terms of thermal resistance.

[0003] Some types of heat dissipation grease are used by being sandwiched between components and then being heated and cured. Many materials have been designed to increase thermal conductivity and improve heat dissipation performance by incorporating a large amount of solid filler. However, in order to reduce the contact thermal resistance with heat-generating and cooling components, it is preferable for the thermally conductive filler to be in contact with the heat-generating and cooling components in a fluid state. From this perspective, various heat dissipation greases containing low-melting point metals have been reported (JP Patent Publication No. 2021-169582, Patent Publication No. 4551074, Patent Publication No. 4860229: Patent Documents 4 to 6). However, since these materials are gallium or alloys containing gallium, there is a risk of corrosion of metal members if gallium is exposed due to stress during operation of the device. In addition, gallium is a rare metal, so it is expensive. On the other hand, JP 2014-003152 A (Patent Document 7) proposes a thermal interface material containing a thermally conductive filler made of a bismuth-tin alloy, but the filler content is insufficient, and it is difficult to say that the thermal resistance is sufficiently reduced. In addition, since the particle size of the filler that is mixed as a spacer is small, the BLT (material thickness) decreases after a heat cycle test, and as a result, it becomes impossible to follow the warp, and there is a risk of the thermal resistance deteriorating due to peeling from the substrate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 2938428 [Patent Document 2] Patent No. 2938429 [Patent Document 3] Patent No. 3952184 [Patent Document 4] Patent Publication No. 2021-169582 [Patent Document 5] Patent No. 4551074 [Patent Document 6] Patent No. 4860229 [Patent Document 7] JP 2014-003152 A Summary of the Invention [Problem to be solved by the invention]

[0005] Accordingly, an object of the present invention is to provide a thermally conductive silicone composition that gives a cured product that has low thermal resistance and excellent reliability. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors conducted intensive research in order to achieve the above object, and as a result discovered that the thermally conductive silicone composition described below was capable of achieving the object, leading to the completion of the present invention. That is, the present invention provides the following thermally conductive silicone composition, etc.

[0007] [1] A thermally conductive silicone composition comprising the following components (A), (B), (C), (D), (E) and (F): (A) A cyclopentasiloxane having at least two alkenyl groups in one molecule and a kinematic viscosity at 25°C of 100 to 500,000 mm 2 / s organopolysiloxane: 100 parts by mass (B) a hydrolyzable methylpolysiloxane having three functional groups at one end and represented by the following general formula (1): 50 to 500 parts by mass per 100 parts by mass of component (A) [ka] (In formula (1), R 1 is an alkyl group having 1 to 6 carbon atoms, and a is a number from 5 to 100. (C) Bismuth-tin alloy powder having a melting point of 220°C or less: 1,000 to 3,000 parts by mass per 100 parts by mass of the total of components (A) and (B) (D) A thermally conductive filler other than component (C) having a melting point of 280°C or higher and an average particle size of 3 μm or more: 200 to 1,500 parts by mass per 100 parts by mass of the total of components (A) and (B) The total of components (C) and (D) is 2,300 to 3,500 parts by mass per 100 parts by mass of the total of components (A) and (B). (E) an organohydrogenpolysiloxane containing at least two hydrogen atoms directly bonded to silicon atoms (Si-H groups) per molecule: an amount such that {the number of Si-H groups in component (E)} / {the number of alkenyl groups in component (A)} is 0.1 to 5.0 (F) a catalyst selected from platinum and platinum compounds: an amount of 0.1 to 500 ppm in terms of platinum atoms relative to the mass of component (A) [2] The thermally conductive silicone composition according to [1], further comprising the following component (G): (G) one or more selected from the group consisting of acetylene compounds, nitrogen compounds, organic phosphorus compounds, oxime compounds, and organic chloro compounds: in an amount of 0.1% by mass to 5% by mass relative to the mass of component (A) Effect of the Invention

[0008] The thermally conductive silicone composition of the present invention contains a bismuth-tin alloy and a filler other than the bismuth-tin alloy that has a specific average particle size, and thus can provide a cured product that has low thermal resistance and excellent reliability.The thermally conductive silicone composition of the present invention is therefore useful as a heat dissipation material for electronic components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below.

[0010] Component (A) The organopolysiloxane of component (A) used in the composition of the present invention has at least two alkenyl groups directly bonded to silicon atoms in each molecule, and may be linear or branched, or may be a mixture of two or more of these with different viscosities. It is preferable that the molecular chain has at least one alkenyl group directly bonded to a silicon atom at each of both ends. Examples of the alkenyl group include a vinyl group, an allyl group, a 1-butenyl group, and a 1-hexenyl group, with the vinyl group being preferred from the standpoint of ease of synthesis and cost. Examples of organic groups other than alkenyl groups bonded to silicon atoms include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and dodecyl groups, aryl groups such as phenyl, and aralkyl groups such as 2-phenylethyl and 2-phenylpropyl groups, as well as substituted hydrocarbon groups such as chloromethyl and 3,3,3-trifluoropropyl groups. Of these, the methyl group is preferred in terms of ease of synthesis and cost. The alkenyl group bonded to a silicon atom is preferably present at the terminal of the molecular chain of the organopolysiloxane.

[0011] The organopolysiloxane of component (A) has a kinematic viscosity at 25°C of 100 to 500,000 mm 2 / s, preferably 400 to 100,000 mm 2 The kinematic viscosity of organopolysiloxane is the value measured at 25°C using an Ostwald viscometer.

[0012] The content of component (A) in the thermally conductive silicone composition of the present invention is preferably 0.1 to 8.0 mass %, more preferably 0.1 to 6.0 mass %, and even more preferably 0.1 to 5.0 mass %. The component (A) may be used alone or in combination of two or more kinds.

[0013] Ingredient (B) The component (B) used in the composition of the present invention is a hydrolyzable methylpolysiloxane having three functional groups at one terminal, which is represented by the following general formula (1). [ka] (In formula (1), R 1 is an alkyl group having 1 to 6 carbon atoms, and a is a number from 5 to 100.

[0014] In the above formula (1), R 1 represents an alkyl group having 1 to 6 carbon atoms, preferably a methyl group, an ethyl group, or a propyl group, and particularly preferably a methyl group or an ethyl group.

[0015] In the above formula (1), a is in the range of 5 to 100, and preferably in the range of 10 to 60. If the above a is less than 5, the oil bleeding of the composition may become severe, resulting in poor reliability, whereas if it is more than 100, the wettability may be insufficient.

[0016] The amount of component (B) is in the range of 50 to 500 parts by mass, and preferably in the range of 100 to 500 parts by mass, per 100 parts by mass of component (A). If the amount of component (B) is less than 50 parts by mass, sufficient wettability may not be exhibited, whereas if it is more than 500 parts by mass, oil bleeding may become severe, resulting in poor reliability. The component (B) may be used alone or in combination of two or more kinds.

[0017] Ingredients (C) Component (C) used in the composition of the present invention is a bismuth-tin alloy powder having a melting point of 220° C. or less. The melting point of component (C) is 220° C. or less, preferably 200° C. or less, more preferably 190° C. or less, and particularly preferably 180° C. or less. If the melting point is higher than 220° C., the alloy may not melt sufficiently in a typical heating process, making it difficult to obtain low thermal resistance. The average particle size of component (C) is preferably in the range of 0.1 to 80 μm, more preferably in the range of 0.1 to 70 μm, and particularly preferably in the range of 0.1 to 60 μm. If the average particle size is smaller than 0.1 μm, the spreadability of the composition may be poor, and if it is larger than 80 μm, it may be difficult to obtain low thermal resistance. In this specification, the average particle size can be measured by a Microtrac MT3300EX manufactured by Nikkiso Co., Ltd., and is a volume-based volume average diameter (the same applies hereinafter). The shape of component (C) may be any shape, including amorphous and spherical.

[0018] The amount of component (C) is in the range of 1000 to 3000 parts by mass, preferably 1000 to 2700 parts by mass, and more preferably 1200 to 2700 parts by mass, per 100 parts by mass of the total of components (A) and (B). If the amount is less than 1000 parts by mass, the substrates may not be sufficiently bonded when heated, and low thermal resistance may not be obtained, whereas if the amount is more than 3000 parts by mass, the spreadability of the composition may be poor. The component (C) may be used alone or in combination of two or more kinds.

[0019] Ingredients (D) Component (D) used in the composition of the present invention is a thermally conductive filler other than component (C) that has a melting point of 280° C. or higher and an average particle size of 3 μm or more. Component (D) preferably has a thermal conductivity of at least 10 W / m° C. If the thermal conductivity is less than 10 W / m° C., the thermal conductivity of the thermally conductive silicone composition itself may end up being low. Examples of component (D) include aluminum powder, copper powder, silver powder, iron powder, nickel powder, gold powder, metallic silicon powder, aluminum nitride powder, boron nitride powder, alumina powder, diamond powder, carbon powder, zinc oxide powder, and aluminum hydroxide powder. However, any filler having a thermal conductivity of 10 W / m°C or more may be used, and one or a mixture of two or more types may be used. The melting point of component (D) is 280° C. or higher, and preferably 300° C. or higher. If it is lower than 280° C., when it is exposed to heating at 260° C., which is typical of lead solder reflow conditions, the thermally conductive filler of component (D) melts, causing the composition to become thinner and less reliable.

[0020] The average particle size of component (D) is 3 μm or more, preferably 3 to 100 μm, more preferably 3 to 80 μm, and particularly preferably 3 to 70 μm. If the average particle size is smaller than 3 μm, the composition may not be able to maintain a sufficient thickness when component (C) is heated and dissolved, resulting in poor reliability after a heat cycle test. If the average particle size is larger than 100 μm, the thermal resistance of the composition may increase, resulting in reduced performance. The shape of component (D) may be any shape, including irregular and spherical.

[0021] The amount of component (D) is in the range of 200 to 1,500 parts by mass, preferably 200 to 1,200 parts by mass, and more preferably 250 to 1,200 parts by mass, per 100 parts by mass of the total of components (A) and (B). If the amount of component (D) is less than 200 parts by mass, the thermal conductivity of the composition may be reduced, and if it is more than 1,500 parts by mass, the dissolution of component (C) may be inhibited. The component (D) may be used alone or in combination of two or more kinds.

[0022] The total amount of components (C) and (D) is in the range of 2,300 to 3,500 parts by mass, preferably 2,300 to 3,300 parts by mass, and more preferably 2,300 to 3,200 parts by mass, per 100 parts by mass of the total of components (A) and (B). If the amount is less than 2,300 parts by mass, the thermal conductivity of the composition may be low, and if it is more than 3,500 parts by mass, the spreadability of the composition may be poor.

[0023] Ingredient (E) Component (E) used in the composition of the present invention is an organohydrogenpolysiloxane having at least two hydrogen atoms directly bonded to silicon atoms (Si-H groups) in each molecule. Examples of organic groups other than Si-H groups bonded to silicon atoms include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and dodecyl, aryl groups such as phenyl, aralkyl groups such as 2-phenylethyl and 2-phenylpropyl, substituted hydrocarbon groups such as chloromethyl and 3.3.3-trifluoropropyl, and epoxy ring-containing organic groups such as 2-glycidoxyethyl, 3-glycidoxypropyl, and 4-glycidoxybutyl. The organohydrogenpolysiloxane of component (E) may be linear, branched, or cyclic, or may be a mixture of these.

[0024] The amount of component (E) blended, {the number of Si-H groups in component (E)} / {the number of alkenyl groups in components (A) and (B)}, is in the range of 0.1 to 5.0, preferably 0.5 to 4.5, and more preferably 0.5 to 2.5. If the amount of component (E) blended, {the number of Si-H groups in component (E)} / {the number of alkenyl groups in components (A) and (B)}, is less than 0.1, the composition cannot be sufficiently reticulated, and the grease may not be sufficiently cured, whereas if it is more than 5.0, the crosslink density may be too high, resulting in poor reliability. The component (E) may be used alone or in combination of two or more kinds.

[0025] Component (F) Component (F) used in the composition of the present invention is a catalyst selected from platinum and platinum compounds, which promotes the addition reaction between the alkenyl groups of components (A) and (B) and the Si-H groups of component (E). Examples of the component (F) include platinum alone, chloroplatinic acid, platinum-olefin complexes, platinum-alcohol complexes, and platinum coordination compounds. The amount of component (F) is in the range of 0.1 to 500 ppm, preferably 0.1 to 400 ppm, in terms of platinum atoms, relative to the mass of component (A). If the amount of component (F) is less than 0.1 ppm in terms of platinum atoms, it will not be effective as a catalyst, and if it is more than 500 ppm, the effect will not increase and it will be uneconomical. The component (F) may be used alone or in combination of two or more kinds.

[0026] Ingredients (G) Component (G) used in the composition of the present invention is an inhibitor that suppresses the catalytic activity of component (F), which is used as needed, and inhibits the progress of the hydrosilylation reaction at room temperature, thereby extending the shelf life and pot life. Known reaction inhibitors can be used, such as acetylene compounds, nitrogen compounds, organic phosphorus compounds, oxime compounds, and organic chloro compounds. The amount of component (G) is preferably 0.1 to 5 mass% relative to the mass of component (A), and more preferably 0.1 to 4 mass%. If the amount of component (G) is less than 0.1%, the shelf life and pot life may not be sufficiently extended, and if it is more than 5%, the curing speed may decrease. The component (G) may be used alone or in combination of two or more kinds. Furthermore, component (G) may be diluted with toluene or the like to improve dispersibility in the thermally conductive silicone composition.

[0027] Other Ingredients In addition to the above components (A) to (G), the composition of the present invention may contain, if necessary, an antioxidant or the like to prevent deterioration.

[0028] Manufacturing method The composition of the present invention can be produced by mixing components (A) to (F), and, if necessary, component (G) and / or other components in predetermined amounts using a mixer such as Trimix, Twinmix, Planetary Mixer (all of which are registered trademarks of mixers manufactured by Inoue Seisakusho Co., Ltd.), Ultra Mixer (registered trademark of mixers manufactured by Mizuho Kogyo Co., Ltd.), or Hivismix (registered trademark of mixers manufactured by Primix Corporation). EXAMPLES

[0029] EXAMPLES In the following, the present invention will be described in more detail with reference to examples and comparative examples in order to clarify the effects of the present invention, but the present invention is not limited thereto. Tests regarding the effects of the present invention were carried out as follows.

[0030] 〔viscosity〕 The absolute viscosity of the composition was measured at 25° C. using a Malcolm viscometer (type PC-10).

[0031] [BLT (material thickness), thermal resistance] A thermally conductive silicone composition was sandwiched between a 15 mm x 15 mm x 1 mmt Si chip and a 15 mm x 15 mm x 1 mmt Ni plate, and while still pressurized at 0.18 (MPa), the composition was heated and cured in a 170°C oven for 90 minutes to prepare a test piece for measuring thermal resistance, and the initial BLT and thermal resistance were measured. Furthermore, a heat cycle test (HC test) was performed under conditions of alternating -40°C for 30 minutes and 125°C for 30 minutes for 1000 cycles, and the BLT and thermal resistance after the test were measured. The BLT was calculated by measuring the thickness of the Si chip and Ni plate with a micro gauge in advance and subtracting it from the overall thickness of the test piece. Thermal resistance measurements were performed using a Nanoflash (NETZSCH, LFA467).

[0032] The following components constituting the composition of the present invention were prepared.

[0033] Component (A) A-1: Both ends are blocked with dimethylvinylsilyl groups, and the kinetic viscosity at 25°C is 600mm 2 / s dimethylpolysiloxane (vinyl value: 0.015 mol / 100 g) A-2: Both ends are blocked with dimethylvinylsilyl groups, and the kinetic viscosity at 25°C is 30,000mm 2 / s dimethylpolysiloxane (vinyl value: 0.0036 mol / 100 g) A-3: Both ends are capped with trivinylsilyl groups, and the kinetic viscosity at 25°C is 1,500mm 2 / s dimethylpolysiloxane (vinyl value: 0.026 mol / 100 g)

[0034] Ingredient (B) B-1: ((CH3)3SiO 1 / 2 )((CH3)2SiO) 30 ((OCH3)3SiO 1 / 2 ) B-2: ((CH3)3SiO 1 / 2 )((CH3)2SiO) 20 ((OCH3)3SiO 1 / 2 )

[0035] Ingredients (C) C-1:Bi 57 Sn 43 Powder Melting point 144℃ Average particle size 19μm C-2:Bi 40 Sn 60 Powder Melting point 142℃ Average particle size 25μm

[0036] Ingredients (D) d-1: Aluminum powder with an average particle size of 10 μm d-2: Aluminum powder with an average particle size of 2 μm d-3: Copper powder with an average particle size of 10 μm d-4: Copper powder with an average particle size of 2 μm d-5: Zinc oxide powder with an average particle size of 0.6 μm The above d-1 to d-5 were mixed in the parts shown in Table 1 below to obtain D-1 to D-5. The results of measuring the average particle size of D-1 to D-5 are also shown below. The average particle size is a value measured as a volume-based volume average diameter using a Microtrac MT3300EX manufactured by Nikkiso Co., Ltd.

[0037] [Table 1]

[0038] Ingredient (E) E-1: Organohydrogenpolysiloxane represented by the following formula: [ka] Si-H content: 0.088mol / 100g E-2: Organohydrogenpolysiloxane represented by the following formula: [ka] Si-H content: 0.137mol / 100g E-3: Organohydrogenpolysiloxane represented by the following formula: [ka] Si-H content: 0.500mol / 100g

[0039] Component (F) F-1: A-1 solution of platinum-divinyltetramethyldisiloxane complex, containing 1 wt% platinum atoms

[0040] Ingredients (G) G-1: 1-ethynyl-1-cyclohexanol

[0041] Examples 1 to 8 and Comparative Examples 1 to 6 The components (A) to (G) were mixed as follows to obtain Examples 1 to 8 and Comparative Examples 1 to 6. That is, component (A) was placed in 1 liter of Hibismix (manufactured by Primix Corporation), and components (B), (C), and (D) were added in the amounts shown in Tables 2 and 3, and mixed for 1 hour. Next, components (E), (F), and (G) were added in the amounts shown in Tables 2 and 3, and mixed until uniform.

[0042] [Table 2]

[0043] [Table 3]

Claims

1. A thermally conductive silicone composition comprising the following components (A), (B), (C), (D), (E), and (F): (A) A copolymer having at least two alkenyl groups in one molecule and a kinematic viscosity at 25°C of 100 to 500,000 mm 2 / s organopolysiloxane: 100 parts by mass (B) a hydrolyzable methylpolysiloxane having three functional groups at one end and represented by the following general formula (1): 50 to 500 parts by mass per 100 parts by mass of component (A) 【Chemistry 1】 (In formula (1), R 1 is an alkyl group having 1 to 6 carbon atoms, and a is a number from 5 to 100. (C) Bismuth-tin alloy powder having a melting point of 220° C. or less: 1,000 to 3,000 parts by mass per 100 parts by mass of the total of components (A) and (B) (D) A thermally conductive filler other than component (C) having a melting point of 280° C. or higher and an average particle size of 3 μm or more: 200 to 1,500 parts by mass per 100 parts by mass of the total of components (A) and (B) The total amount of components (C) and (D) is 2,300 to 3,500 parts by mass per 100 parts by mass of the total amount of components (A) and (B). (E) an organohydrogenpolysiloxane containing at least two hydrogen atoms directly bonded to silicon atoms (Si—H groups) per molecule: an amount such that {the number of Si—H groups in component (E)} / {the number of alkenyl groups in component (A)} is 0.1 to 5.0 (F) a catalyst selected from platinum and platinum compounds: an amount of 0.1 to 500 ppm in terms of platinum atoms relative to the mass of component (A)

2. The thermally conductive silicone composition according to claim 1 , further comprising the following component (G): (G) one or more selected from the group consisting of acetylene compounds, nitrogen compounds, organic phosphorus compounds, oxime compounds, and organic chloro compounds: in an amount of 0.1% by mass to 5% by mass relative to the mass of component (A)

Citation Information

Patent Citations

  • JP1973060229A

  • Method for forming thermal interface material and heat dissipation structure

    JP2014003152A

  • Thermally conductive silicone composition

    JP2021169582A

  • Thermal conductive grease composition

    JP2938428B1

  • Thermal conductive silicone composition

    JP2938429B1